Phenomenon Of Verbal Bullying In The Pedawang Society - Sheila Rizky Amalida Putri; Erik Aditia Ismaya; Much Arsyad Fardani (NATURALISTIC : Jurnal Kajian Penelitian Pendidikan dan Pembelajaran, 2021)
This study aims to determine the forms and factors of verbal bullying in children and the impact of verbal bullying on children’s self confidence in Pedawang Village. The research method used is descriptive qualitative. The researcsubjects were three children in Pedawang Village. Based on the research result, there are two kinds of forms and factors of verbal bullying, namely verbal bullying based on nicknames and verbal bullying based on physical forms. Victims of verbal bullying become less confident about themselves, this is evidenced by the vicims tho become quiet and insecure about themselves while paling together. From the results of the study, it was also found that the occurrence of verbal bullying was only for a joke to his friend, not to hurt the feelings of other.